Pengaruh Kualitas Pelayanan dan Kepercayaan Terhadap Niat Nasabah Menggunakan Jasa di LPD Desa Adat Buduk (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2026)
This research aims to determine the effect of service quality and customer trust on the intention of customers to use services at the LPD of Buduk Customary Village. The population in this study consists of all customers of the LPD of Buduk Customary Village, totaling 6,420 customers in savings, deposits, and loans. This research used a sample of 98 respondents based on the Slovin formula. The sample was determined using accidental sampling with data collection methods including observation, interviews, documentation, and questionnaires. The data analysis techniques used in this study include testing the research instrument, classical assumption tests, and multiple linear regression analysis with the help of SPSS Windows version 24. The results of this study indicate that 1) service quality has a positive and significant effect on the intention of customers to use services at LPD Desa Adat Buduk. 2) trust has a positive and significant effect on the intention of customers to use services at LPD Desa Adat Buduk. 3) both service quality and trust have a positive and significant effect on the intention of customers to use services at LPD Desa Adat Buduk. Suggestions that can be made for LPD Desa Adat Buduk include regularly conducting evaluations of employee performance, ensuring the safety of customer funds, and adding premium products for customers.